Investigating Soil Management Practices for Sustainable Coffee Cultivation in Kambuga Town Council Kanungu District. - Asiimwe, Hillary (Kabale University, 2024)
This study examined soil management practices for sustainable coffee cultivation in Kambuga Town Council, Kanungu District. Its objectives were to assess the effectiveness of current practices, identify soil nutrient deficiencies affecting coffee yields, and explore strategies to improve production. A descriptive research design was employed, gathering data from 90 coffee farmers through structured questionnaires and semi-structured interviews. The findings revealed widespread use of soil conservation methods, with mulching (60.3%) and terracing (49.2%) being the most common techniques. While 40% of farmers applied fertilizers monthly, 60% did not regularly test their soil. Awareness of soil nutrient deficiencies was high (80%), with nitrogen (62.5%), phosphorus (41.7%), and potassium (27.8%) identified as key deficiencies significantly affecting yields. Effective soil management strategies included mulching (75.6%) and erosion control (50%). However, farmers faced challenges such as knowledge gaps, high costs, and limited resources.